Structural and related studies on Mevo lectin from Methanococcus voltae A3: the first thorough characterization of an archeal lectin and its interactions. (11th July 2020) - Sivaji, Nukathoti; Suguna, Kaza; Surolia, Avadhesha; Vijayan, Mamannamana
Abstract: Crystallographic and solution studies of Mevo lectin and its complexes, the first effort of its kind on an archeal lectin, reveal a structure similar to β-prism I fold lectins from plant and animal sources, but with a quaternary association involving a ring structure with seven-fold symmetry. Each subunit in the heptamer carries one sugar binding site on the first Greek key motif. The oligomeric interface is primarily made up of a parallel β-sheet involving a strand of Greek key I of one subunit and Greek key ΙΙΙ from a neighboring subunit. The crystal structures of the complexes of the lectin with mannose, αMan(1, 2)αMan, αMan(1, 3)αMan, a mannotriose and a mannopentose revealed a primary binding site similar to that found in other mannose specific β-prism I fold lectins. The complex with αMan(1, 3)αMan provides an interesting case in which a few subunits have the reducing end at the primary binding site, while the majority have the nonreducing end at the primary binding site. The structures of complexes involving the trisaccharide and the pentasaccharide exhibit cross-linking among heptameric molecules. The observed arrangements may be relevant to the multivalency of the lectin. Phylogenetic analysis of amino acid sequences indicates that Mevo lectin is closer to β-prism I fold animal lectins than with those of plant origin. The results presented here reinforce the conclusion regarding the existence of lectins in all three domains of life. It would also appear that lectins evolved to the present form before the three domains diverged.